2013
DOI: 10.1016/j.jhsa.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Supercharge Nerve Transfer to Enhance Motor Recovery: A Laboratory Study

Abstract: Purpose To investigate the ability of a supercharge end-to-side (SETS) nerve transfer to augment the effect of regenerating native axons in an incomplete rodent sciatic nerve injury model. Methods Fifty-four Lewis rats were randomized to 3 groups. The first group was an incomplete recovery model (IRM) of the tibial nerve complemented with a SETS transfer from the peroneal nerve (SETS-IRM). The IRM consisted of tibial nerve transection and immediate repair using a 10mm fresh tibial isograft to provide some, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 50 publications
3
72
0
Order By: Relevance
“…Recently Farber and Mackinnon [30] demonstrated the positive effect of a supercharged nerve transfer in an experimental study based on peroneal nerve transfers in rats, which demonstrated improvements resulting from the double axonal charge. This technique was then later used in the treatment of patients with brachial plexus injuries with similar improvements in outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Farber and Mackinnon [30] demonstrated the positive effect of a supercharged nerve transfer in an experimental study based on peroneal nerve transfers in rats, which demonstrated improvements resulting from the double axonal charge. This technique was then later used in the treatment of patients with brachial plexus injuries with similar improvements in outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and Mackinnon demonstrated that neurolysis of the ulnar nerve can be performed up to 14 cm proximal to the radial styloid. 4 The reverse end-to-side or "supercharge" nerve transfer 40,41 can also increase intrinsic function and allow the ulnar nerve to recover spontaneously also. 42 In 1997, Wang and Zhu demonstrated transfer of the anterior interosseous nerve to the ulnar motor branch or to the thenar branch of the median nerve in cadavers and clinically but did not differentiate the outcomes.…”
Section: Median Nerve Injurymentioning
confidence: 99%
“…It provides a fast muscle re-innervation with preservation of the muscle bulk until the axons of the damaged nerve regenerate and reach their own endplates [66]. This avoids muscle atrophy while the injured nerve axons regenerate [71]. It has been used successfully in the case of anterior interosseous nerve (AIN) to motor fascicle of the UN transfer [52].…”
Section: End-to-end Anastomosismentioning
confidence: 99%
“…The clinical outcome is very satisfactory [29,62,152]. Another possibility is a reverse end-to-side transfer, avoiding atrophy of the UN innervated hand muscles while awaiting for the native UN motor axons to regenerate [70,71,154]. It is very effective [29].…”
Section: Ulnar Nerve Hand Functionmentioning
confidence: 99%